Pengembangan Bahan Ajar Berbasis Etnofotografi Benda-Benda Bersejarah Masa Penyebaran Hindu-Buddha di Kabupaten Batang untuk Mata Pelajaran IPS di Sekolah Dasar - Yulista, Yulista; Purnamasari, Iin; Saputro, Bagus Ardi (Universitas PGRI Semarang, 2023)
This study aims to determine the practicality, and effectiveness of ethnophotography-based teaching materials in social studies learning in elementary schools. This research is research and development by adopting the ADDIE model (analysis, design, development, implementation, and evaluation). The analysis phase includes an initial needs analysis. The design stage includes closing, instructions for use, table of contents, mapping of Basic Competencies, general knowledge, introduction, presentation, exercises, glossary, answer keys and table of contents. The development stage is making teaching materials covering aspects, content of material, validation and display of production of ethnophotography-based teaching materials, development of instrument data. The data collection instruments in this study were the feasibility of lecturers, practicality sheets for subject teachers and peers, student readability sheets, pretest and posttest questions for student learning outcomes. The data collection instrument is based on the learning of the supervisor, assessment by experts, subject teachers, peers and student trials. The implementation phase of the use of teaching materials that have been developed for fourth grade students at SDN Karangasem 13. The trials carried out at this stage were product feasibility tests, readability, and pretest posttests for fourth grade students, with the results showing an increase in learning outcomes after students used ethnophotography-based teaching materials. evidenced by the n-gain value of 0.49 in the medium category. The evaluation stage includes the form of evaluation carried out at each stage of the ADDIE model. The data analysis technique used is the manova test and n-gain. The results showed that the ethnophotography teaching materials developed were suitable for use in social studies learning. The ethnophotography teaching materials are practical to use, and effective to improve the learning outcomes of elementary school students.